Effect of vibration frequencies on the welding properties of rectangular mild steel plate - Hussein, Alaa Raad (2010)
The welding process induces potential deflection, which significantly affects the ultimate strength behavior of the welded structure. The deflection can result in many problems that can have an adverse effect of the accuracy of the assemblage part, external appearance or strength characteristics ot the welded metal. The main aim of this study is to identify a relationship between the induced vibration and welding temperature including the properties of welding in order to obtain the deflection that occurs on the plate’s surface. In addition, the effect of frequency during welding on the mechanical properties of the welding fusion metal was also investigated. Four different values of frequencies were investigated (3, 5, 10 and 100) Hz and applied on a rectangular plate with dimension (400 x 200 x 6) mm. The strain was measured at the area close to the middle surface and on the transverse direction (at the edge, 20, 40, 60 and 90) mm from the edge. The theoretical results showed that the maximum value of the deflection occurs at the middle surface and it decreases on the transverse direction downward to the edge. Further more the effect of varying temperature and frequency on the measured strain provides the same behavior of deflection at the middle surface and it decreases on the transverse direction downward to the edge, which started at 3.9 micro strain at the edge when both of welding and 100 Hz are applied and kept increasing to reach the maximum value at the middle 7.8 micro strain when the 100Hz are applied. The applied vibration during welding resulted in an improvement of about 50% for tensile strength and maxmum load of 29076.68 N for the ductility of the filler metal due to the fine distribution of the filler metal by the effect of vibration. The increase in the frequency value during welding process led to reduce the micro crack that generated inside the fusion filler metal which generated because of high welding temperature. In conclusion, the applied frequency and thermal load at the centre of the plate surface generate plate deflection and resulted in less value of deflection on the transverse direction than the centre. In addition, these forces led to increase in the strain value at the centre of the plate. The applied vibration during welding results in a fine distribution of the filler metal and increased the ductility and the tensile strength of the filler metal. This increasing in the mechanical properties provides a good indicator of the positive effect of induced vibration on welds.